Faktor yang Berhubungan dengan Kejadian Diabetes Melitus pada Masyarakat Usia >45 Tahun - Yana, Hida; Usrina, Nora; Irdayani; Dewi, Nova Ratna; Norisa, Nanda; Hanum, Nisrina; Zakaria, Radhiah (Lembaga Teewan Journal Solutions, 2026)
Diabetes mellitus (DM) is a chronic metabolic disorder whose increasing prevalence poses a major public health challenge. Adults aged 45 years and older are particularly vulnerable because of age-related changes in glucose metabolism. This study aimed to identify factors associated with DM among adults aged ≥45 years in Bener Meriah Regency. This cross-sectional study included 235 residents of Mekar Ayu Village, Timang Gajah District, selected using total population sampling. Data on dietary patterns, lifestyle, and sleep patterns were collected using questionnaires, while diabetes status was determined through blood glucose measurement. Data were analyzed using univariate analysis, the chi-square test, and multiple logistic regression with a 95% confidence interval. Diabetes was identified in 64 participants, resulting in a prevalence of 27.2%. Dietary patterns, lifestyle, and sleep patterns were significantly associated with the condition. Poor dietary patterns were the strongest associated factor. Participants with poor dietary patterns had 6.54 times higher odds of having DM than those with healthy dietary patterns after adjustment for lifestyle and sleep patterns (AOR = 6.54; 95% CI: 3.22–13.27; p < 0.001). The findings indicate that diabetes is relatively prevalent among adults aged ≥45 years in the study area, with dietary patterns as the most dominant associated factor. Community health centers should strengthen nutrition education, practical dietary counseling, promotion of active lifestyles and healthy sleep habits, and regular screening of high-risk adults.